2009
DOI: 10.1111/j.1365-2265.2008.03411.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased epicardial adipose tissue (EAT) volume in type 2 diabetes mellitus and association with metabolic syndrome and severity of coronary atherosclerosis

Abstract: The analytical results indicate that EAT volume is increased in T2DM patients and is associated with unfavourable components of MetS and coronary atherosclerosis. The close anatomical relationship between EAT and the coronary arteries, combined with other evidence indicating that EAT is a biologically active adipokine-secreting tissue, suggest that EAT participates in the pathogenesis of diabetic coronary atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
163
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(190 citation statements)
references
References 30 publications
21
163
2
4
Order By: Relevance
“…25 EFV is an important fat depot and its abundance was clearly associated with the presence and severity of coronaropathy. 8,15,40 An inflammatory profile in patients with coronary disease was also enlightened, suggesting a pathophysiological link between EFV and the development or aggravation of coronaropathy. 5,8,9,41 This study provides a detailed characterization of the metabolic, inflammatory and cardiovascular parameters associated with EFV.…”
Section: Discussionmentioning
confidence: 99%
“…25 EFV is an important fat depot and its abundance was clearly associated with the presence and severity of coronaropathy. 8,15,40 An inflammatory profile in patients with coronary disease was also enlightened, suggesting a pathophysiological link between EFV and the development or aggravation of coronaropathy. 5,8,9,41 This study provides a detailed characterization of the metabolic, inflammatory and cardiovascular parameters associated with EFV.…”
Section: Discussionmentioning
confidence: 99%
“…13 Many studies have concluded that EAT is higher in the patients with diabetics, HT and obesity. [6][7][8][21][22][23] DM and HT are closely related with the metabolic syndrome and the two most frequently observed reasons of the increased cardiovascular risk in the general population and the ESRF patients. No study has been recorded yet which addresses uremic factors and its relationship with EAT in the dialysis patients without DM and HT.…”
Section: Discussionmentioning
confidence: 99%
“…5 Various studies point that as a part of metabolic syndrome EAT has increased in both Type 1 and Type 2 diabetes patients and hypertensive patients and that this may be a new cardiovascular risk indicator. [6][7][8][9] However, the number of studies pointing that EAT may be taken as a cardiovascular risk indicator in patients with ESRF is very few. In a small number of recent studies, it has been pointed that EAT and coronary artery calcification score in patients with ESRF has increased in comparison with healthy people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using transthoracic echocardiography showed that epicardial adipose tissue thickness measured on the right ventricle correlated with waist circumference, abdominal visceral fat, insulin resistance, metabolic syndrome, and the severity of coronary artery disease [6] [16] [17] [18]. A number of studies using cardiac CT also showed that the amount of epicardial adipose tissue was associated with cardiovascular risk factors, coronary artery calcification, metabolic syndrome, and diabetes, independent of recognized obesity-related indicators such as BMI or waist circumference [19] [20] [21] [22] [23].…”
Section: Discussionmentioning
confidence: 99%